Cass's Homosexual Identity Formation: A Critical Analysis. Issue 4 (5th October 2021) - Goodrich, Kristopher M.; Brammer, M. Kathryn
Abstract : Cass's (1979) model of homosexual identity formation has been used as a guideline to understand sexual identity development, although questions of its current applicability have been raised. This article critically analyzes Cass's model through a contemporary lens. To contextualize and understand the model and its implications, we review empirical and anecdotal research, as well as several human processes. Implications for counselors and counselor educators and suggestions for best use of the model are provided. El modelo de formación de la identidad homosexual de Cass (1979) ha sido utilizado como una guía para comprender el desarrollo de la identidad sexual, aunque han surgido dudas sobre su validez en la actualidad. Este artículo analiza de forma crítica el modelo de Cass desde una perspectiva contemporánea. Para contextualizar y comprender el modelo y sus implicaciones, revisamos las investigaciones empíricas y anecdóticas, además de varios procesos humanos. Se proporcionan implicaciones para consejeros y educadores en consejería, así como sugerencias sobre la mejor forma de utilizar el modelo.